Replacing Fallow with Cover Crops in a Semiarid Soil: Effects on Soil Properties. Issue 3 (10th May 2013) - Blanco-Canqui, Humberto; Holman, John D.; Schlegel, Alan J.; Tatarko, John; Shaver, Tim M.
Abstract : Replacement of fallow in crop–fallow systems with cover crops (CCs) may improve soil properties. We assessed whether replacing fallow in no‐till winter wheat ( Triticum aestivum L.)–fallow with winter and spring CCs for 5 yr reduced wind and water erosion, increased soil organic carbon (SOC), and improved soil physical properties on a Ulysses silt loam (fine‐silty, mixed, superactive, mesic Aridic Haplustolls) in the semiarid central Great Plains. Winter triticale (× Triticosecale Wittm.), winter lentil ( Lens culinaris Medik.), spring lentil, spring pea ( Pisum sativum L. ssp.), and spring triticale CCs were compared with wheat–fallow and continuous wheat under no‐till management. We also studied the effect of triticale haying on soil properties. Results indicate that spring triticale and spring lentil increased soil aggregate size distribution, while spring lentil reduced the wind erodible fraction by 1.6 times, indicating that CCs reduced the soil's susceptibility to wind erosion. Cover crops also increased wet aggregate stability and reduced runoff loss of sediment, total P, and NO3 –N. After 5 yr, winter and spring triticale increased SOC pool by 2.8 Mg ha –1 and spring lentil increased SOC pool by 2.4 Mg ha –1 in the 0‐ to 7.5‐cm depth compared with fallow. Triticale haying compared with no haying for 5 yr did not affect soil properties. Nine months after termination, CCs had, however, no effects on soil properties, suggesting that CC benefits are short lived in this climate. Overall, CCs, grown in each fallow phase in no‐till, can reduce soil erosion and improve soil aggregation in this semiarid climate.